STUDY ON THE EFFECT OF READING ACTIVITIES AND LISTENING TO AL-QURAN ON HUMAN MENTAL HEALTH - Nadimah, Nuha Arie (Journal Intellectual Sufism Research (JISR), 2018)
Health problems are a major concern for creating people's welfare, both physical and mental health. The intended mental health is a mental emotional disorder, which includes stress and depression. Spiritual education as a human need in life, which is related to worship such as activities related to the Qur'an. Literacy studies need to be carried out regarding the influence of the Qur'anic book on the human body related to the human mind that can influence mental, emotional, and memory health. The results obtained based on literature studies in this study indicate that the Qur'an has a positive impact on mental health and is able to delay cognitive aging (memory enhancement)